The law book - Chrisp, Peter; Cock-Starkey, Claire; Cowell, Frederick; Cussans, Thomas; Farndon, John; Parker, Philip; Weeks, Marcus (Big ideas simply explained., 2020)
Why do we need laws? What rights are protected by law? When was forensic evidence first used in court? This book explores big questions like these, explaining the laws and legal precedents, and religious, political, and moral codes that have shaped the world we live in. Written in plain English, The Law Book cuts through the legal jargon and is packed with pithy explanations of the most important milestones in legal history, with step-by-step diagrams and witty illustrations that untangle knotty concepts.--